DSP Based Power Quality Analyzer for Detection and Classification of Disturbances in a Single-Phase Power System - Radil, Tomas (2009)
This paper describes the prototype of a power quality analyzer designed for real-time detection and classification of disturbances that occur in a single-phase power system. The standalone DSP-based analyzer implements previously developed algorithms for detection and classification of power quality disturbances such as transients, waveform distortions, sags, swells and interruptions. Its performance was verified during long term monitoring of the power system.